Penatalaksanaan Fisioterapi Kontrol Postural pada Kasus Global Delay Development di School and Therapy Talitakum Semarang - Khairunnisa, Fatimah As-Syifa; Amanda, Tasya Ghea (Academic Physiotherapy Conference Proceeding, 2023)
Introduction: Pregnancy-related Pelvic Girdle Pain (PGPP) is the most common condition during pregnancy that affects the quality of life, and a previous study has found that between 17% to 64.7% of pregnant women reported PPGP worldwide. The physiotherapy management of PPGP has varieties among countries, especially in the low- and middle-income countries (LMICs) group setting which are dependent on their country’s situations. The topics that need to discover more in the LMICs were the vulnerable maternal and neonatal morbidity and mortality risk factors. This could be the inadequate health service quality, lack of information, limited coverage, and low quality of antenatal care. Case Presentation: A literature review from five databases (PubMed, Pedro, Science Direct, Cochrane, and Web of Science). A mix of keywords has been used in the search or Medical Subject Heading (MESH) terms related to "pregnancy-related pelvic girdle pain" or “Pelvic Girdle Pain AND Pregnancy” and combine with OR treatment and "low and middle-income countries". The inclusion criteria of the articles were that pregnant women aged 18 years old suffered PPGP and all studies assessed the published in English within 2000-2020. The methodological quality of the included studies in terms of internal validity was assessed using CASP (Critical Appraisal Skills Program). Management and Outcome: lumbopelvic belts could improve functional status, decreased the level and intensity of pain, and raise the quality of life among pregnant women were the benefit of physiotherapy management for solving the PPGP problems. Discussion: Four articles have been selected from five databases with 80% of quality assessment for each research. The studies mentioned 3 to 10 weeks exercise program, a specific exercise program (pelvic rocking technique, back care, routine prenatal care, home-based pelvic stabilizing exercise), and lumbopelvic belts could improve functional status, decreased the level and intensity of pain, and raise the quality of life among pregnant women were the benefit of physiotherapy management for solving the PPGP problems. Conclusion: Physiotherapy management in the LMICs group setting use the three to ten weeks of exercise program. The specific technique of exercise and lumbopelvic belts were used to treat the PPGP problems among pregnant women.